Assessment of the Spatial Distribution and Mapping Soil Physico-Chemical Properties of Nalgad Municipality, Jajarkot, Nepal (Journal of Agriculture and Environment, 2022)
A detailed soil inventory study using Global Positioning System (GPS) and Geographical Information System (GIS) was conducted in Nalgad Municipality of Jajarkot, Nepal in 2019. A preliminary reconnaissance survey during pre–field activities and detail field work was carried out to study the soil type and physico-chemical properties based on the soil pit. A total of 51 soil pits were taken in the field representing varied micro topography. Soil Sample pits covering all the units were dug based on the interpreted soil map, topographical map, ZY-3 Satellite imagery for determination of soil profile. Soil classification of the area was done based on the USDA soil taxonomy and the dominant soil orders found in the region were Entisols (15.13 %) and Inceptisols (83.60%). A total of 51 geo-referenced composite soil samples from a depth of 0-20 cm was collected from each pit and analyzed in laboratory for texture, soil pH, soil organic matter, total nitrogen, available phosphorus and exchangeable potassium. Majority of the soil are loam and loamy sand type. There is very low to high level of organic matter present in the study area with more proportion of land under high range of organic matter (64.98%). Total Nitrogen content in soil of the study area ranges from very low to very high level with high level of Nitrogen (65.51%) in major proportion. Low to very high level of available phosphorous content was found in the study area with the dominance of very high level of phosphorous (71.40%). Exchangeable Potassium level in the study area is very high to low. Around 42% land have very high level of potassium. From the soil test result, major nutrients status in soil were found to be good but integrated land management practices should be encouraged for improving land productivity. The generated soil maps may be helpful to stakeholders for planning, monitoring and evaluating the soil status for effective agricultural production.